Predicting Diagnostic Gene Biomarkers Associated With Immune Infiltration in Patients With Acute Myocardial Infarction - Zhao, Enfa; Xie, Hang; Zhang, Yushun (Frontiers in Cardiovascular Medicine, 2020)
Objective: The present study was designed to explore potential diagnostic markers for acute myocardial infarction (AMI) and investigate the significance of immune cells infiltration in this pathology. Methods: Two public available gene expression profiles (GSE66360 and GSE48060 datasets) from human AMI and control samples were downloaded from the Gene Expression Omnibus (GEO) database. Differentially expressed genes (DEGs) were identified between 80 AMI and 71 control samples. Least absolute shrinkage and selection operator (LASSO) model and support vector machines recursive feature elimination (SVM-RFE) analysis were performed to identify the candidate biomarkers. From the receiver operating characteristic (ROC) curve, the area under the ROC curve (AUC) value was obtained and used for evaluating discriminatory ability. The expression level and diagnostic value of biomarkers in AMI were further validated in GSE60993 dataset (17 AMI patients and 7 controls). The compositional patterns of 22 types of immune cell fraction in AMI were estimated based on the merged cohorts using Cell type Identification by Estimating Relative Subsets of RNA Transcripts (CIBERSORT). Results: A total of 27 genes were identified. The identified DEGs are mainly involved in carbohydrate binding, Kawasaki disease, atherosclerosis, and arteriosclerotic cardiovascular disease. Gene-sets related to atherosclerosis signaling, primary immunodeficiency, IL-17 and TNF signaling pathways were differentially activated in AMI compared to control. IL1R2, IRAK3 and THBD were identified as diagnostic markers of AMI (AUC = 0.877), and validated in the GSE60993 dataset (AUC = 0.941). Immune cell infiltration analysis revealed that IL1R2, IRAK3 and THBD were correlated with neutrophils, monocytes, M2 macrophages, CD4+ resting memory T cells, T cells gamma delta, and activated NK cells. Conclusion: IL1R2, IRAK3 and THBD can be used as diagnostic markers of AMI, and provides novel evidence and clues for future research of the occurrence and molecular mechanisms of AMI.